A spatial analytic approach for classifying greenspace and comparing greenspace social equity. (May 2017) - Kimpton, Anthony
Abstract: Urban planners frequently adhere to 'park minimum standards' to ensure that public health and environmental benefits associated with greenspace are socially equitable. These standards denote the extent and placement of greenspaces, but rarely consider their form and function. Arguably, an inclusive evaluation of greenspace social equity requires the comparison of greenspace types. To address if greenspace types are socially equitable, I develop a novel spatial analytic approach that classifies 4265 greenspaces according to twelve functional, physical characteristics. I then compare the social equity of these greenspace types using multiple operationalizations of social equity (provision, accessibility, and population pressure) throughout 4524 neighborhoods in a capital city in Australia. I find that greenspace social equity varies for each of these types. For example, results reveal that affluent households have an abundance of amenity rich greenspaces and few amenity poor ones. Further, by comparing across multiple social equity operationalizations, I find that affluent households may have a deficit of the amenity poor greenspace type, but live closer to this type. These findings confirm that employing a greenspace typology and multiple social equity operationalizations can deepen our understanding of the association between social equity and greenspace provision. This spatial analytic approach is both adaptable for examining other urban land use types, and portable to other urban contexts, and can aid urban planners, researchers, and policy makers to understand how to improve the social equity of publicly beneficial greenspace types. Highlights: Identifies three conceptually distinct measures of greenspace social equity. Introduces an objective greenspace shape measure. Demonstrates a cluster analysis as a method to objectively classify greenspace. Reveals that operationalization influences greenspace social equity findings. Reveals greenspace social equity varies according to greenspace type.